Bacteria‐Mediated Tumor Therapy via Photothermally‐Programmed Cytolysin A Expression. Issue 40 (1st September 2021) - Wang, Longyu; Qin, Wenjun; Xu, Wenxuan; Huang, Fan; Xie, Xiaochen; Wang, Fei; Ma, Lixin; Zhang, Cheng
Abstract: By leveraging the ability of bacteria to express therapeutic protein cytolysin A (ClyA) through plasmid transformation, a thermally‐activated biohybrid (TAB@Au) is constructed by biomineralizing gold nanoparticles (AuNPs) on the E. coli surface. Due to the feature of anaerobic bacteria homing to tumor microenvironments, the bacteria‐based antitumor vehicles can be efficaciously accumulated at tumor sites. Under NIR laser irradiation, the biomineralized AuNPs harvest transdermal photons and convert them into local heat for photothermal therapy. After that, the produced heat elicits the expression of ClyA for killing tumor cells. In vitro and in vivo experiments verify the conception that the current therapeutic modality greatly inhibits the proliferation of tumor cells. In terms of the spatial specificity and non‐invasiveness of NIR laser, the bacteria‐based phototherapy represents an appealing way for tumor therapy. Abstract : By leveraging the intrinsic ability of microorganisms, a thermally‐activated biohybrid (TAB@Au) is constructed by biomineralizing gold nanoparticles on E. coli surface. Under laser irradiation, the generated local heat is utilized for PTT and elicited the expression of cytolysin A to strengthen treatment.